Seasonal Index and Breeding Efficiency of Red Chittagong Cattle in Bangladesh (Journal of Tropical Resources and Sustainable Science (JTRSS), 2013)
The study was aimed to observe reproductive pattern and efficiency of Red Chittagong Cattle (RCC) including reproductive history taken from two different herds; nucleus herd (on-station) and community herd (on-farm) in Mymensingh district of Bangladesh. A total of 184 calving parity records from 66 RCC cows that included 317 estrous, 164 conception and 178 calving history covering a period from 2005 to 2011 were considered for analyses. The highest frequencies of estrous, conception and calving occurred in May (13%, 15% and 14%, respectively), while the lowest in September for estrous (4%) and conception (4%) and April and June for calving (5%). The month of the year had significant (p
Keywords: Calving index; Reproductive efficiency; Seasonal influence; Red Chittagong; cattle; Estrus